A CASE OF GUILLAIN-BARRE SYNDROME-A RARE AUTOIMMUNE MEDIATED INFLAMMATORY NEUROPATHY PRECEDED BY CAMPYLOBACTER JEJUNI. - MANJULA DEVI.A.J.; VASANTHAN.M. (International Journal of Pharma and Bio Sciences, 2014)
Autoimmune diseases are becoming quiet common among the population. these diseases are difficult to diagnose but, once diagnosed they are curable in most cases when treated earlier. here, we are going to discuss a case of guillain-barre syndrome,an autoimmune disease and the early treatment which helps in the cure.